2021
DOI: 10.33087/ekonomis.v5i2.409
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Ukuran Perusahaan, Ukuran Dewan Komisaris, Dan Pengungkapan Modal Manusia Terhadap Kinerja Perusahaan di Indonesia

Abstract: This study aims to empirically prove the effect of firm size, board of commissioners and human capital disclosure on firm’s performance of consumer goods industry companies listed on the Indonesia Stock Exchange from 2015 - 2019. The independent variables in this study are firm size, board of commissioners, and human capital disclosure with the dependent variable is firm’s performance. The sample used in this study is data from consumer goods industry companies listed on the Indonesia Stock Exchange for the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
2
0
2
Order By: Relevance
“…Salah satu indikator untuk menunjukkan besar atau kecil sebuah perusahaan adalah ukurannya. Ketika sebuah perusahaan memiliki asset atau sumber daya yang besar, perusahaan tersebut diperkirakan akan menggunakan atau memaksimalkan sumber dayanya untuk menghasilkan keuntungan atau profit yang besar, argumen ini sepemahaman dengan Davinda et al, (2021) bahwa perusahaan dengan asset yang besar lebih mampu menghasilkan laba yang besar dibandingkan dengan perusahaan yang terbilang lebih kecil. Perusahaan kecil memiliki sumber daya yang terbatas sehingga belum mampu untuk memaksimalkan keuntungannya.…”
Section: Pengembangan Hipotesisunclassified
“…Salah satu indikator untuk menunjukkan besar atau kecil sebuah perusahaan adalah ukurannya. Ketika sebuah perusahaan memiliki asset atau sumber daya yang besar, perusahaan tersebut diperkirakan akan menggunakan atau memaksimalkan sumber dayanya untuk menghasilkan keuntungan atau profit yang besar, argumen ini sepemahaman dengan Davinda et al, (2021) bahwa perusahaan dengan asset yang besar lebih mampu menghasilkan laba yang besar dibandingkan dengan perusahaan yang terbilang lebih kecil. Perusahaan kecil memiliki sumber daya yang terbatas sehingga belum mampu untuk memaksimalkan keuntungannya.…”
Section: Pengembangan Hipotesisunclassified
“…Osangkul, Treepongkaruna, Jiraporn and Uyar (2021) found that firms tend to reduce board size in response to economic policy uncertainty. Meanwhile, several recent studies have suggested that larger board numbers are positively associated with better firm performance (Mai, 2015;Farooque et al, 2019;Punni & Anlesinya, 2020;Davinda et al, 2021;Sheikh & Alom, 2021;Ramadan & Hassan, 2021). The more member of boards can provide knowledge and experience to supervise managers and help solve problems (Farooque et al, 2019).…”
Section: Board Of Commissioners Size and Firm Performancementioning
confidence: 99%
“…Fadillah (2017) found that an increasing proportion of independent commissioners will cause the firm performance to decrease. Mai (2015), Davinda, Mukhzarudfa, and Zulma (2021) found that board size positively affect firm performance. Several studies on companies with a one-tier board system, have investigated the positive influence of the board on company performance (Farooque, Buachoom, & Sun, 2019;Puni & Anlesinya, 2020;Sheikh & Alom, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Salah satu parameter kontrol dalam meningkatkan kinerja perusahaan adalah ukuran dewan komisaris dengan jumlah besar (Davinda et al, 2021). Kinerja perusahaan yang baik maka akan meningkatkan nilai perusahaan.…”
Section: Dewan Komisarisunclassified